House rental management system for student in UiTM Perlis / Nur Nadiah Husna Samsudin and Muhammad Nabil Fikri Jamaluddin - Samsudin, Nur Nadiah Husna; Jamaluddin, Muhammad Nabil Fikri (College of Computing, Informatics and Media, UiTM Perlis, 2023)
This House Rental Management system is a system created to display rental houses near UiTM Perlis that are available. This house rental management system will also display detailed information about each house and allow you to contact the agent via WhatsApp. The purpose of the House Rental Management System is to help students find available rental houses near campus. While, in this system also can give landlords to upload their house to display in this system. So it can give ease to student to contact them for rent their house. The methodology used for the development process is the waterfall model. The entire project development process is divided into separate phases. It will go through three phases, such as system requirement identification, system design and development, and testing. Besides functional testing, also user acceptance test (UAT) with 30 participants, consisting of students from UiTM Perlis, was conducted to verify the performance of this system prototype.